Cfd Of Double-Wedge Spiked Intake Of The Supersonic Jet Engine - Dhinakaran Govindasamy, Dhinakaran Govindasamy (Universiti Teknologi Petronas, 2010)

(untitled)
Intake of the Supersonic Jet Engine requires the highest possible total pressure recovery and minimal total pressure lost in order to obtain an efficient operation. The supersonic intake is mainly affected by two substantial factors which is the geometry of the spike (double-wedge) and the angle of attack. The solution is quite direct at zero angle of attack, but at non zero angle of attack, the shock system structure will be affected and the flow distribution will be unsymmetrical in the upper (leeside) and the lower side (windward side) of the inlet. The objective of this work is to model mathematically the double-wedge spiked intake of the supersonic jet engine. The analysis will be carried out using the assumptions that the flow is viscous, steady and 2-dimensional compressible fluid flow. The whole system will be simulated and analysed numerically using CFD softwares. The available FLUENT and GAMBIT software in the department will be used for the modelling simulation. Finally this model will be used to investigate the flow characteristics at various design and operational conditions. In conclusion, the study of on the combined effect of the double-wedged spike and angle of attack is crucial as it affects the performance of the compressor, which then affects the performance of the jet engine.